2018
DOI: 10.1088/1757-899x/326/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Two-Phase Oil (D130)-Water Flow in 4″ Pipe for Different Inclination Angles

Abstract: Abstract. Oil and water are often produced and transported together in pipelines that have various degrees of inclination from the horizontal. The flow of two immiscible liquids oil and water in pipes has been a research topic since several decades. In oil and chemical industries, knowledge of the frictional pressure loss in oil-water flows in pipes is necessary to specify the size of the pump required to pump the emulsions. An experimental investigation has been carried out for measurement of pressure drop of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…A good agreement has been noticed specifically with the Blasius friction factor. The related equations and graphs are reported in our earlier studies [28,29].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A good agreement has been noticed specifically with the Blasius friction factor. The related equations and graphs are reported in our earlier studies [28,29].…”
Section: Methodsmentioning
confidence: 99%
“…Similar procedure was followed for other angles including; 40°, 60° 90° and for different water cut ratio 0 to 100%. Inlet oil-water flow rates were varied from 2000 to 12000 barrels-per-day (BPD) [28,29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have attempted to predict pressure gradients in horizontal and vertical flows using empirical models [4][5][6]. Only very few studies considered inclined flows [7,8]. Liu et al [7] developed flow pattern-based correlations to predict the frictional pressure gradient in tilted smooth tubes.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [20] found that the flow patterns affect the frictional pressure drop. Shaahid et al [21] analyzed the effects of different inclination angles on the two-phase frictional pressure drop. In addition, Ganat et al [22] proposed a new method of the frictional pressure drop for the oil-water-gas three-phase flow.…”
Section: Introductionmentioning
confidence: 99%